Entrepreneurship and innovation toolkit - Swanson, Lee A.; BC Open Textbook Project; BCcampus (Lee A. Swanson, 2017)
"This book provides an overview of the world of entrepreneurship. Topics covered include an introduction to entrepreneurship; opportunity recognition and design thinking; evaluation entrepreneurial opportunities; business models; business planning; financing entrepreneurship; business set-up, start-up, and growth; strategic entrepreneurship; innovation and entrepreneurship; and the entrepreneurial."--BCcampus website.
Chapter 1. Introduction to Entrepreneurship -- Chapter 2. Opportunity Recognition and Design Thinking -- Chapter 3. Evaluating Entrepreneurial Opportunities -- Chapter 4. Business Models -- Chapter 5. Business Planning -- Chapter 6. Financing Entrepreneurship -- Chapter 7. Business Set-Up, Start-Up, and Growth -- Chapter 8. Strategic Entrepreneurship -- Chapter 9. Innovation and Entrepreneurship -- Chapter 10. The Entrepreneurial Environment.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed January 22, 2020).
Keywords: Entrepreneurship -- Textbooks; Electronic books